Feminisms and Democracy - FERREIRA DE MELLO, NICOLI (Temporalidades, 2021)
The book, published in 2019 and organized by Joana Maria Pedro and Jair Zandoná, comprises eighteen chapters of sum-summaries of debates from the 3rd LEGH Day and the experiences of the very daily life of feminist struggles, in order to highlight the mobilizations in the most varied spaces. In addition, it highlights the different strategies used to reflect and resist, considering the "Spring of Women" of 2015 in Brazil, as well as those carried out during dictatorial regimes that occurred in Latin America. In this way, it demonstrates the importance of the pluralism of Feminisms, resistance and Democracy itself.